Balancing acts: Navigating school, work, and life among female pre-service teachers in the Philippines - Remojo, Joy Angelle B.; Cacho, Reynald (Journal of Interdisciplinary Studies in Education, 2026)
Balancing school, work, and personal life presents significant challenges for emerging young adult female students in pre-service teacher education programs. This qualitative study examined their lived experiences via a phenomenological approach. Five participants were selected through purposive sampling, and data were collected through semi-structured online interviews and analyzed using Colaizzi’s method. Key challenges included time conflicts, role strain, and emotional stress. Despite prioritizing academics and personal well-being, participants demonstrated resilience, supported by family, faculty, and peers. They employed self-regulation and adaptability to cope. The study recommends flexible academic policies, responsive school programs, enhanced financial aid, on-campus jobs, faculty training, and industry collaboration to reduce burdens and improve academic success for working students